2016
DOI: 10.3928/01913913-20160405-07
|View full text |Cite
|
Sign up to set email alerts
|

The Degree of Anisocoria in Pediatric Patients With Horner Syndrome When Compared to Children Without Disease

Abstract: In a study of 592 children without Horner syndrome, the average pupillary size increased with age, but the degree of anisocoria remained stable with increasing age. Over half of the children studied had anisocoria up to 0.5 mm (62.84%), but rarely had anisocoria greater than 1.3 mm (3.70%). In children with a diagnosis of Horner syndrome, the majority had anisocoria greater than 1.3 mm, with the discrepancy in pupil size becoming more apparent in low levels of light intensity. Anisocoria greater than 1.3 mm is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
4
5
0
Order By: Relevance
“…This is consistent with the study done by Suh et al, in which 100% of the 32 diagnosed Horner syndrome patients had associated ptosis [4]. In addition, the study by Suh also found that 9.4% of the patients had anhidrosis [4].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This is consistent with the study done by Suh et al, in which 100% of the 32 diagnosed Horner syndrome patients had associated ptosis [4]. In addition, the study by Suh also found that 9.4% of the patients had anhidrosis [4].…”
Section: Discussionsupporting
confidence: 91%
“…This finding was in accordance with the study by Suh et al [4]. In addition, given that only five of the patients had pupil size data available, physicians should be reminded to measure pupil size to determine the degree of anisocoria when it is present.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations